Penguatan Administrasi Keuangan Dan Literasi Finansial Anak Melalui Program Kp2m: Studi Kasus Di Desa Ketawang, Malang - Dyatri Utami Arina Absari; Devinda Kristanti; Mike Yuliska; Aftoniah Aftoniah; Muhammad Riyan Mahmud Syam (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
Strengthening financial governance and financial literacy within rural communities plays a vital role in achieving sustainable village development. The Community Service and Empowerment Program (Kuliah Pengabdian dan Pemberdayaan Masyarakat/KP2M) conducted in Ketawang Village, Malang Regency, employed two main approaches: assistance in village financial administration and gamification-based financial literacy education for children. The methods applied included participatory approaches, field observations, and gamified educational activities. The results indicated increased transparency and openness among village officials in managing financial administration, along with heightened awareness and enthusiasm among children in recording and managing their pocket money in a simple manner. This program contributes to strengthening community financial independence while instilling a culture of disciplined administration and early financial management habits Keywords: Village financial administration, Children's financial literacy, Gamification, KP2M, Transparency.